2019
DOI: 10.1111/gcb.14722
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic nitrogen enrichment enhances soil carbon accumulation by impacting saprotrophs rather than ectomycorrhizal fungal activity

Abstract: There is evidence that anthropogenic nitrogen (N) deposition enhances carbon (C) sequestration in boreal forest soils. However, it is unclear how free‐living saprotrophs (bacteria and fungi, SAP) and ectomycorrhizal (EM) fungi responses to N addition impact soil C dynamics. Our aim was to investigate how SAP and EM communities are impacted by N enrichment and to estimate whether these changes influence decay of litter and humus. We conducted a long‐term experiment in northern Sweden, maintained since 2004, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 88 publications
7
47
1
1
Order By: Relevance
“…There is growing consensus that added N generally reduces soil microbial biomass (Treseder, 2008;Liu and Greaver, 2010;Lu et al, 2011;Zhou et al, 2017), which in turn drives reductions in decomposition and soil respiration (Janssens et al, 2010;Riggs and Hobbie, 2016). Yet common, this response is not universal (Waldrop et al, 2004a;Keeler et al, 2009;Riggs et al, 2015;Heuck et al, 2018) but contingent on, for example, ecosystem type (Yue et al, 2016), experimental duration (Treseder, 2008), N load (Maaroufi et al, 2019), or sampling year (Gutknecht et al, 2012;Contosta et al, 2015). For instance, in a recent meta-analysis MBC increased under low N loads (<50 kg N ha −1 yr −1 , similar levels as applied at both study sites here) but did not respond above that levels (Yue et al, 2016).…”
Section: Long-term N Addition and Soil Microbes: Effects On Biomass Amentioning
confidence: 72%
“…There is growing consensus that added N generally reduces soil microbial biomass (Treseder, 2008;Liu and Greaver, 2010;Lu et al, 2011;Zhou et al, 2017), which in turn drives reductions in decomposition and soil respiration (Janssens et al, 2010;Riggs and Hobbie, 2016). Yet common, this response is not universal (Waldrop et al, 2004a;Keeler et al, 2009;Riggs et al, 2015;Heuck et al, 2018) but contingent on, for example, ecosystem type (Yue et al, 2016), experimental duration (Treseder, 2008), N load (Maaroufi et al, 2019), or sampling year (Gutknecht et al, 2012;Contosta et al, 2015). For instance, in a recent meta-analysis MBC increased under low N loads (<50 kg N ha −1 yr −1 , similar levels as applied at both study sites here) but did not respond above that levels (Yue et al, 2016).…”
Section: Long-term N Addition and Soil Microbes: Effects On Biomass Amentioning
confidence: 72%
“…The decline in fungal biomass was largely attributed to a decrease in ectomycorrhiza, which form associations with trees, suggesting that fungi are more sensitive to long-term N fertilization than bacteria. Most previous research focused on soil bacterial communities in forests (Shen et al, 2010;Turlapati et al, 2013), and we are aware of only a few studies that examined changes in soil fungal community composition following increased N loads (Boxman et al, 1998;Allison et al, 2007;Edwards et al, 2011;Maaroufi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the humus substrate, we observed a net C gain (Figure 2f), which is somewhat unusual in decomposition studies. However, humus has not been used as often as needles in decomposition studies, and previous studies using humus as a decomposition substrate have shown it is very resistant to decomposition, with mass loss typically below 10% per year (Bödeker et al, 2016;Maaroufi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For the humus substrate, we observed a net C gain (Figure 2f), which is somewhat unusual in decomposition studies. However, humus has not been used as often as needles in decomposition studies, and previous studies using humus as a decomposition substrate have shown it is very resistant to decomposition, with mass loss typically below 10% per year (Bödeker et al., 2016; Maaroufi et al., 2019). In addition to the recalcitrance of the humus in general, the specific humus we used had a relatively high nutrient content compared to the surrounding soil matrix (Table 1; Figure 1), which may have stimulated fungal ingrowth causing this substantial C accrual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation